Zeitlichkeit und Geschichtlichkeit des bewegten Bildes in der Gegenwartskunst - Steinmüller, Nina (Brill, 2021)
Time and temporality are not only inherent to the moving image because it is time-based, but also because it is able to reflect on time - through its materialization in the image, through the revelation of distinct layers of time, or by disturbing and disrupting the transparency of the narrating image. In works of contemporary art, the temporality of the moving image interconnects with its historicity.